2005
DOI: 10.1007/s10681-005-4713-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci (QTL) of stem strength and related traits in a doubled-haploid population of wheat (Triticum aestivum L.)

Abstract: Scoring for lodging resistance is difficult under natural field conditions. The stem strength of wheat has been used as an index of lodging resistance. However, this is a complex trait comprised of two characters, i.e. stem mechanical elasticity and rigidity. Therefore it is closely associated with stem morphological and anatomical features. A study of the genetics of stem strength and related traits of basal stem internodes is very important for genetic improvement of lodging resistance in wheat. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 34 publications
(26 reference statements)
2
44
0
Order By: Relevance
“…However, extreme dwarfism is also associated with decreased biomass, shrunken seeds, premature senescence, and increased susceptibility to diseases, resulting in reduced yield (Allan 1986;Islam et al 2007). Furthermore, even after dwarfing, lodging may still occur if stem strength is weak (Hai et al 2005;Ma 2009), therefore increasing stem strength will be a very promising strategy to breed soybean with high lodging resistance. As one of the key influencing factors of lodging, stem strength (resiliency of stem) is significantly correlated with lodging resistance in soybean (Mancuso and Caviness 1991;Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, extreme dwarfism is also associated with decreased biomass, shrunken seeds, premature senescence, and increased susceptibility to diseases, resulting in reduced yield (Allan 1986;Islam et al 2007). Furthermore, even after dwarfing, lodging may still occur if stem strength is weak (Hai et al 2005;Ma 2009), therefore increasing stem strength will be a very promising strategy to breed soybean with high lodging resistance. As one of the key influencing factors of lodging, stem strength (resiliency of stem) is significantly correlated with lodging resistance in soybean (Mancuso and Caviness 1991;Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…SS was measured using a prostrate tester made in Japan (DIK-7400, Daiki Soil and Moisture). The prostrate tester was set perpendicularly to the plants at 20 cm height, when plants inclined to 45°from the vertical, pushing resistance was measured, and estimated using the following formula: SS (gram per stem) = test value/40 9 1,000 (Kashiwagi and Ishimaru 2004;Hai et al 2005). At maturity stage, lodging (LD) was recorded according to the methods described by Lee et al (1996).…”
Section: Plant Materials Field Experiments and Traits Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that lignin synthesis and accumulation might be related to stem strength (Jones et al, 2001;Pedersen et al, 2005;Ma, 2009). This creates a major problem in monocotyledonous crop plants in which poor culm strength leads to a lodging phenotype (Hai et al, 2005;Ma, 2009). The selection and breeding processes, which aim to prevent plant lodging, lead to the creation of dwarf and semi-dwarf phenotypes of barley cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that plants' lodging-resistances were positively correlated with stem's diameter [16]. After a wheat double haploid line was gotten by hybridizing the line CA9613 and H1488, the physical strength of the stem and the characters of the basic stem were measured at milk stage [17]. Six QTLs are responsible for physical strength of stem, thickness of stem wall, pore diameter and stem diameter were found in 1A, 2D, 3A, and 3B [17].…”
mentioning
confidence: 99%